Metallurgical failure investigation of small bore piping (SBP) in a diesel hydrotreating unit (DHT) of an oil refinery - Cagliyan, E.; Fischer, B.; Giller, M.; Neidel, A. (Praktische Metallographie, 2024)
Hydrocarbon leaks were repeatedly found in the client’s refinery. Because of the recurring nature of this failure, the operator approached the authors’ laboratory to get a second opinion on the metallurgical root cause of the failure. It was known from the customer that corrosive species, such as ammonium chloride salt precipitates, are present in the subject diesel hydrotreating unit (DHT). From the findings obtained in the investigation that is the subject of this contribution, the conclusion of the original metallurgical root cause analysis (RCA), namely that the subject piping failed by transgranular chloride-induced stress corrosion cracking (Cl-SCC), could be verified and is indeed correct. The metallurgical root cause of the small bore piping (SBP) failure is chloride-induced SCC. The morphology of the cracking is very distinct and is clearly consistent with transgranular Cl-SCC. A material change to the nickel-base material Alloy 625, already considered by the client, since this alloy is believed to be immune to chloride-induced SCC, would be a good, even though expensive solution. It should be emphasized that there are no metallic materials completely resistant to SCC. If the environment is harsh enough, except for some titanium alloys, i. e., if the source of the chloride ions cannot be eliminated, which is likely the case here, a regular inspection and replacement of these SBP systems might have to be considered. It should further be emphasized that a chloride concentration below 50 ppm is by no means any guarantee for the avoidance of SCC, since chlorides can concentrate in crevices, corrosion pits and such, i. e., the local concentration is what matters, not the local.